RELIGIÃO PROFÉTICA E CRISE POLÍTICA: Um estudo da sociedade norte-israelita à luz de Oséias 9,1-9. - Ferreira, Vicente Luíz Simões (2008)
With the development of this research project Prophetic religion and political crisis: the study of the North Israeli society by the light of Hosea 9,1-9 we want to identify which moment of the crisis was that, which the North Israeli society had gone through in the 7th Century B.C., and which would be the hoseanic background that had worked as a leitmotiv in their prophetic life. Instead of starting from a regression, e.g., from a deductive study (descendent method), due to the lack of material and also for the complexity of the work, I will do the opposite, I will start from the theory that today is fully acceptable in the academic environment. Based on a methodology that favors the results achieved from the most precise historiographic data critic historical methods and archaeological researches this research project will make use of the inductive method e.g. we will start from a rising process. The challenge is in outlining the autonomic path of the North Israeli monarchy, trying to stabilish what were the most marked moments from this historical way, susceptible to forge the manifestation of the prophets, such as Amos, Hosea, Micah and many others. As the main object of our research, the focus will be on prophet Hosea who knew as nobody else before him, to make a synthesis between religion and life, e.g., he knew how to develop ethical criterions that were of use as evaluating parameter of purity in the javista religion.